First record of alatoconchid bivalves from the Middle Permian Maokou Formation in central Hubei, South China - Yang, Liangzhe; Wu, Kui; Wang, Wei; Yang, Boyong; Yang, Di; Yuan, Siyu; Yu, Haoyu; Cui, Yasheng (Frontiers in Earth Science, 2025)
This study reports the first discovery of bivalves (family Alatoconchidae) from the Middle Permian Maokou Formation in Jingmen City, Hubei Province, South China. These newly identified fossil localities bridge a significant geographic gap in alatoconchid distribution, providing new insights into their paleobiogeography and paleoecology. Their frequent occurrence in warm, shallow-marine environments supports the view that South China provided an ideal ecological setting for these organisms during the Guadalupian. Furthermore, the absence of alatoconchids in younger strata suggests their extinction was closely linked to the Guadalupian-Lopingian boundary mass extinction event.